Politický zeměpis střední Evropy (Czech Journal of International Relations, 1992)
Ludwik Mazurkiewicz: Human Geography in Eastern Europe and the Former Soviet Union. Belhaven Press, London, Halsted Press, New York, Toronto 1992, 163 stran.